The IDB and the Caribbean : partners for growth and opportunity (IDB WashingtonUS, 2009)
Begins with a broad picture of the Caribbean regional economy. Presents highlights of selected IDB partnerships in the Caribbean that have had significant impacts on human well-being and expanded possibilities for growth, institutional development and economic transformation. Concludes with a summary of IDB programmes in each of the countries.
Keywords: IDB